Functional Outcomes of Proximal Humerus Fractures with PHILOS in a Tertiary Care Setup - Khatana, Naveed Hussain; Hafeez ur Rehman; Siyal, Shahjahan; Mehmood, Usman; Iqbal, Saad; Abdul Rafay (Indus Journal of Bioscience Research, 2024)
Background: Proximal humerus fractures are favorably classified according to AO classification and NEERS classification. Proximal humeral internal locking system (PHILOS) is representative of locking plates. In spite of being superior to conventional plates PHILOS is associated with complications. Objective: To determine the functional outcomes of proximal humerus fractures treated by PHILOS (Prximal Humerus Interlocking Osteo-synthesis system). Material and Methods: Overall 94 patients were included and operated using PHILOS by deltoid splitting approach. Patients were discharged on 3rd postoperative day. Skin staples were removed at 15th day. Arm was kept in polysling for 3 weeks. After 3 weeks pendulum exercises and range of motion exercises were started. Functional outcomes were assessed by Constant shoulder score at 6 weeks and 3 months. Descriptive statistics were calculated. Stratification was done and post-stratification chi square test was applied considering p-value ≤0.05 as significant. Results: Total 68.1% patients were male and 31.9% were female. The mean constant murley’s shoulder score after 6 weeks and 3 months was 57.10±7.02 and 87.54±9.64. as per Neer classification 9.6% had part-II, 81.9% had part-III and 8.55 had part-IV fracture. The functional outcome assessed by constant shoulder score status showed 59.6% had moderate and 40.4% had poor after 6 weeks and after 3 months 74.5% had excellent, 18.1% had good and 7.4% had moderate outcome. Conclusion: In our study, 74.5% patients had excellent, 18.1% had good and 7.4% had moderate functional outcome at end of follow-up after 3 months.